2013
DOI: 10.1108/01437731311289947
|View full text |Cite
|
Sign up to set email alerts
|

“It's not you, it's me”: transformational leadership and self‐deprecating humor

Abstract: Purpose -The purpose of this paper is to investigate leaders' use of humor as an expression of how they value themselves relative to others. The paper suggests that humor can minimize or exacerbate the status differences between leaders and followers. The paper hypothesizes that leaders' use of self-or in-group-deprecating humor would be positively associated with ratings of transformational leadership as they minimize those distinctions, whereas leaders' use of aggressive humor would be negatively associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 62 publications
6
42
1
3
Order By: Relevance
“…It would be positive for the practitioners to initiate the creation of such conditions by ensuring that the nonphysical environment facilitates the generation of what Fine & Wood (2010) call a 'joking surround.' This would be a space where, arguably, affiliative humour-that oils the wheels of social interaction, creating a sense of common ground and lessening perceived social gaps between people (Vaillant, 1977;Hoption et al, 2013) would thrive.…”
Section: Resultsmentioning
confidence: 99%
“…It would be positive for the practitioners to initiate the creation of such conditions by ensuring that the nonphysical environment facilitates the generation of what Fine & Wood (2010) call a 'joking surround.' This would be a space where, arguably, affiliative humour-that oils the wheels of social interaction, creating a sense of common ground and lessening perceived social gaps between people (Vaillant, 1977;Hoption et al, 2013) would thrive.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical research shows that when leaders use self-defeating humor, the score of personalized care index is high. But when leaders used offensive humor, they scored lower on measures of personalized care [19]. Wisse and Rietzschel (2014) studied the relationship between self-defeating humor and leader-member exchange (LMX), and found that self-defeating humor of leaders positively affected leader-member exchange, which was positively moderated by subordinate self-derogatory humor [20].…”
Section: The Influence Of Humorous Leader On Leadershipmentioning
confidence: 99%
“…The TLs can be defined as a leader's behavior that inspires his/her followers to perform beyond expectations and transcending self-interest to the interest of the organization [6]. Its dimensions are (1) idealized attributes, (2) idealized behaviors, represents a set of attributes and behaviors which make the leader as a role model by subordinates, (3) Individualized consideration, it focuses on the communication and behaviors between the leader and his/her subordinates [7], (4) Intellectual stimulation, is related to the ability of the leader to convince subordinates to need to abandon old ways of thinking and adopt creative ways [8], (5) Inspirational motivation means the leaders' ability to articulate a vision while demonstrating optimism and enthusiasm [9]. The TLs dimensions were and still are the field of the researchers to know its relationship and influence on a lot of behaviors, such as organizational learning, job satisfaction, turnover etc.…”
Section: A Relationship Between Transformational Leadership and Indimentioning
confidence: 99%